SISTEM PENILAIAN KINERJA KARYAWAN BERBASIS WEB PADA PT.WIFIKU INDONESIA - Refni Wahyuni; Yuda Irawan (Jurnal Rekayasa Perangkat Lunak dan Sistem Informasi, 2021)
AHP is able to help the employee selection process recipient an incentive to perform matrix calculations pairs criteria weights, then get the highest priority. Based on the highest priority, determined which alternative will be recommended. The purpose of this research is to make performance appraisal which can facilitate quickly assess performance. Steps for assessing employee performance such that designing concepts, data collection, preparation of hardware and software, display design, system manufacturing, testing and evaluation. Based on the research that has been done it is concluded that the media system is web-based employee performance appraisal at PT. Wifiku Indonesia has successfully created.